The role of vocational education in the context of ensuring the national security of Ukraine - Gren, L. N.; Karlyuk, S. V. (National University of Civil Defence of Ukraine, 2019)
The article discloses the functions of vocation-and-technical training in society that influence ensuring of a country’s national security; there is proved the need in state management of vocation-and-technical training’s development to raise efficiency of its operation in various activity spheres in the interests of national security of Ukraine.
Keywords: state security; education activities; vocation-and-technical training; functions of vocation-and-technical training